Tesla: beyond overvalued- will Tesla meet the market expectations? - Harrak, Malik (2021)
The renewable segment is great to enhance Tesla brand recognition of a futuristic sustainable company yet is constantly growing at a slower pace than expected by the company, which continuously hurts its credibility; even though we expect it to start presenting some results in the next five years, we do not believe it to have the same scale as the EV segment. Our valuation model discloses a Target share price of $342.17 at YE 2021, a (51.51%) downside from the current market price. A detailed scenario analysis was performed, indicating that even in an ideal scenario where every assumption is pushed to the reasonable extreme to benefit Tesla, the share price will be 543.97, enforcing our sell recommendation.